Figure 3 from: Sikes D, Stockbridge J (2013) Description of Caurinus tlagu, new species, from Prince of Wales Island, Alaska (Mecoptera, Boreidae, Caurininae). ZooKeys 316: 35-53. https://doi.org/10.3897/zookeys.316.5400 - Sikes, Derek; Stockbridge, Jill (Zenodo, 2013)
Figure 3 - Inferred phylogeny from Bayesian analysis. Each terminal is a single specimen with the UAM cryovial barcode of its DNA extraction indicated by a six digit number. Branch support is indicated as estimated posterior probability from the Bayesian analysis first and maximum-likelihood bootstrap percentages second. Branch lengths are proportional to the number of substitutions per site as reconstructed by MrBayes 3.2. Specimen 242224 is the holotype of Caurinus tlagu http://arctos.database.museum/guid/UAM:Ento:142986. The remaining three Caurinus tlagu specimens correspond to the following paratypes in Table 1: 242222 (UAM:Ento:135818), 242225 (UAM:Ento:159119), and 242226 (UAM:Ento:154335).